Influence Size Company, Profitability, Liquidity, and Solvency of Audit Delay with the Reputation of the KAP as Variable Moderating on Company Manufacture Which Registered in BEI in the Year of 2017 – 2020 - Devi Faradilah; Tifania Agitha br. Tarigan; Wilsa Road Betterment Sitepu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Study this aim for look for know influence size company, profitability, liquidity, and solvency on audit delay with KAP reputation as a moderating variable. Types of research this is quantitative with secondary data originating from BEI (www.idx.com) and sample in this study, 65 manufacturing companies were listed on the IDX in 2017 – 2020. Results This study states that firm size, liquidity and solvency have an effect on audit delay , profitability has no effect on audit delay , and firm size, profitability, liquidity, and solvency have no effect on audit delay with KAP reputation as a variable moderating.